Applying the Financial Sustainability Standard and its Impact on the Bank’s Value: Evidence from the Iraqi Market - Al-Gburi, Dr. Hayder Jameel Ahmed; Ali Wahhab, Asaad Mohammed (Technium Sustainability, 2023)
The objective of this study is to assess the impact of applying the sustainability standard to the financial sector (commercial banks) for a representative sample of banks listed on the Iraq Stock Exchange. The financial statements of eight commercial banks for 2015–2021 were analysed in accordance with the disclosure requirements of the financial sustainability standard for commercial banks to accomplish the study objectives. Tobin's Q scale was implemented to measure the impact and value of a company using a regression model. Statistical methods (model of linear regression and ETA coefficient) were also employed to assess the study hypotheses. According to the research, there is an effect between non-financial reporting, the sustainability standard of commercial banks, and the value of the company, and this effect is inversely negative because the level of non-financial disclosure is below the required level.